2016
DOI: 10.1021/acsbiomaterials.5b00398
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Mesoporous Silica Nanoparticles Delivering Arsenic Trioxide with Environment Sensitive Drug Release for Effective Treatment of Triple Negative Breast Cancer

Abstract: In this study, we report a novel modality of using a mesoporous silica nanoparticles (MSNs)-based drug delivery system with RGD peptide as a targeting ligand to load arsenic trioxide (ATO) (ATO-MSNs-RGD) for treating MDA-MB-231 triple-negative breast cancer. The MSNs, ATO-MSNs, and ATO-MSNs-RGD were characterized by X-ray diffraction (XRD), thermogravimetric analysis (TGA), transmission electron microscopy (TEM), and Brunauer-Emmet-Teller (BET) method. The data indicated that the MSNs possessed MCM-41 type mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 31 publications
1
39
1
Order By: Relevance
“…Comparison of this value with the number of thiols per gram of thiolated MSN(5 nm pores) (0.4 mmol of –SH/g) shows that this corresponds to a 1:2 molar ratio of As:thiols, implying that at full capacity two sulfhydryl groups are binding to each arsenic atom. This ATO loading capacity is also notably lower than that reported by Wu et al of 120 mg/g 39 and Muhammad et al of 46 mg/g 36 for other thiolated MSN preparations, likely as a result of a lower surface area (580 m 2 /g vs 1021 m 2 /g for Wu et al and 728 m 2 /g for Muhammad et al) and thiol content (0.4 mmol of –SH/g vs 1.1 –SH/g for Wu et al) of the MSN used in this work. Despite this, a loading capacity of 20 mg of ATO per gram of MSN is sufficient to deliver therapeutic quantities of 0.1–1 mg of ATO/kg with MSN doses of <50 mg of MSN/kg, which have been shown to be safe in murine models.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…Comparison of this value with the number of thiols per gram of thiolated MSN(5 nm pores) (0.4 mmol of –SH/g) shows that this corresponds to a 1:2 molar ratio of As:thiols, implying that at full capacity two sulfhydryl groups are binding to each arsenic atom. This ATO loading capacity is also notably lower than that reported by Wu et al of 120 mg/g 39 and Muhammad et al of 46 mg/g 36 for other thiolated MSN preparations, likely as a result of a lower surface area (580 m 2 /g vs 1021 m 2 /g for Wu et al and 728 m 2 /g for Muhammad et al) and thiol content (0.4 mmol of –SH/g vs 1.1 –SH/g for Wu et al) of the MSN used in this work. Despite this, a loading capacity of 20 mg of ATO per gram of MSN is sufficient to deliver therapeutic quantities of 0.1–1 mg of ATO/kg with MSN doses of <50 mg of MSN/kg, which have been shown to be safe in murine models.…”
Section: Resultscontrasting
confidence: 68%
“…Recent efforts to increase the therapeutic index of ATO have utilized a variety of nanoparticle-based drug delivery methods including liposomes, 2831 polymeric nanoparticles, 3235 and most recently mesoporous silica nanoparticles. 3639 …”
Section: Introductionmentioning
confidence: 99%
“…This targeting strategy relies on the overexpression of some receptors only on the membrane of tumoral cells. Examples of this approach include the functionalization of the particles with antibodies [122,123], proteins [69,124], small molecules [125][126][127][128][129] or peptides [77,130,131], among others.…”
Section: Nanotechnology For Cancer Treatmentmentioning
confidence: 99%
“…In order to address this issue, we intend to incorporate mesoporous silica nanoparticles (MSNs) into the PVA nanofibrous mats to achieve long time drug release. Lots of previous research studies had demonstrated the potential of MSNs as drug carriers for the controlled release of therapeutics owing to their high surface area, large pore volume, regular and adjustable pore size, and a hydrophilic surface character . The rich pore structure of MSNs enables extraordinarily large loadings of drugs.…”
Section: Introductionmentioning
confidence: 99%